Wyobraźnia badacza – od serii przekładowej do serii recepcyjnej - Skwara, Marta (Wydawnictwo Poznańskie Studia Polonistyczne i Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2014)
The author addresses the problem of translation series, demonstrating that the rich tradition of creating and researching such series focused mainly on structural and model analyses, and usually isolated translations from other reception phenomena related to a foreign text in a national culture. By shifting the attention from translation-only studies to research in a wider scope of reception of a foreign text, such as intertextual relations of originals/translations with national literature/ culture, comments, and the work performed around a foreign text and its translation (e.g. convention of an editing series, anthology editing, canon creation), the author proposes to introduce three complementary notions: translation series, textualisation series, reception series. The author also discusses the proposals on specific examples derived from the Polish reception of Walt Whitman’s poetry.
Researcher’s imagination – from translation series to reception series
Keywords: translation studies; comparative criticism; reception of foreign text